Legal Implications and Challenges of Informal Sale and Purchase Binding Agreements (PPJB): The Role of Notaries in Ensuring Legal Validity and Protection - Azzahra, Sani (Universitas Islam Negeri Sumatera Utara, 2025)
The Preliminary Sale and Purchase Agreement (PPJB) is often executed informally, primarily due to practical considerations such as incomplete payments or unfinished land administration. Although legally binding, informal PPJB agreements are vulnerable to legal challenges, especially when there is ambiguity regarding the subject matter or failure to fulfill obligations. Therefore, the role of notaries in ensuring legal validity is crucial. This study aims to explore the legal implications and challenges in drafting PPJB, particularly concerning the notary's role in ensuring that the agreement meets legal standards and provides sufficient protection for the involved parties. This research adopts a normative legal methodology, utilizing secondary data sources, including relevant legal provisions, scholarly articles, and case studies. The analysis is conducted descriptively, focusing on the legal framework governing PPJB and the involvement of notaries. The findings indicate that PPJB, while legally binding, can be easily contested if executed informally. Notarial PPJB offers stronger legal protection. However, challenges such as differing interpretations and unclear property rights transfer procedures persist. Notaries play a critical role in ensuring the legal validity of PPJB. Legal clarity and proper documentation are essential to avoid disputes in land transactions